THE CHALLENGE OF RISING EDUCATIONAL COSTS - Glen, Joan (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1971)
For some time now it has been a generally accepted view that all expenditures on education must be inherently desirable. When a thing is good, the reasoning goes, more of it must he better. If educational costs have increased beyond all expectations, it is a burden that must be born, for surely expenditures on education are an indicator of the progress and enlightenment of a society. Moreover, economists have demonstrated that investment in human capital is an essential spur to economic growth. As we move on through the seventies, however, economic realities may force a re-assessment of the priorities that have been granted to education as a form of social expenditure. If this is to he so, educators should be the first, and not the last, to recognize the problem, to analyse the situation and to propose practical solutions.